Micro Macro Economics Fundamental Factors and Indonesia Stock Exchange Return - Rizaldi Yusfiarto (EkBis: Jurnal Ekonomi dan Bisnis, 2019)
Stock investment has an attraction for investors because with investments in the form of shares, investors have the expectation of obtaining profits in the form of capital gains or stock dividends. To take into account the risk factors and produce a maximum level of profit, the stock purchase decision-making process requires careful analysis when determining its market value. Thus, in deciding investment in the stock market, prospective investors must first conduct an in-depth analysis of the company whose shares will be purchased. The fundamental analysis concerns the projected condition of the company in the future by showing the present and past situations. This approach is used to assess the intrinsic value of these shares, and investors are used for investment over a long period. The data used in this research are 22 infrastructure issuers on the Indonesia Stock Exchange from 2015-2018. The data is then processed by the econometrics method using Eviews and Microsoft Excel software with a panel data regression model or pooled regression. Hypothesis testing shows that fundamental macro-micro factors jointly affect the stock returns on infrastructure companies listed on the Indonesia Stock Exchange